Clima organizacional para el desempeño laboral (2019)
This degree work presents the analysis of the Labor Climate in organizations and how it influences the productivity of each of the areas of the company and its direct or indirect impact on both corporate and individual goals and objectives. Subsequently, the analysis of the ideal elements of the work environment with which a company must have is presented so that the performance of its employees is as expected, or even exceeds organizational expectations.